Disabling barriers experienced by students with disabilities in postsecondary introductory physics - Westley James (American Physical Society, 2020)
Educators and education researchers in postsecondary physics have rarely centered (i.e., intentionally directed attention to) the experiences of students with disabilities, leading to an instructional environment that is not designed to support students with disabilities. In this study, we interviewed five students who identified with the diagnosis of attention-deficit/hyperactivity disorder (ADHD) and were enrolled in introductory physics courses at a public four-year institution. We framed our investigation with a social relational perspective of disability, which posits that an individual’s impairments (referred to as diagnosis characteristics in this paper) interact with social structures to result in disabling barriers (i.e., characteristics of social structures which prevent equal access for individuals with disabilities). We analyzed interview transcripts with interpretative phenomenological analysis (IPA). We found that the participating students discussed diagnosis characteristics including difficulties with focus, being prone to distractions, difficulties with keeping mental track of tasks and structures, and thinking often about abstract concepts. Diagnosis characteristics identified as challenges could result in negative self-perceptions, possibly as a result of internalized ableism. However, students also expressed that understanding their diagnosis led to benefits such as making more informed choices about their study strategies (e.g., using a planner or chunking their studying time). In alignment with our social relational perspective of disability, we found that course design could support or hinder participants’ ability to use their preferred planning or studying strategies. We also found that students experienced increased barriers in their physics courses compared to other courses, specifically due to the increased time needed to process information and a lack of guidance for how to effectively study content for conceptual understanding. SCALE-UP courses introduced supports due to increased student autonomy but could also introduce barriers due to increased distractions. We present recommendations that instructors can implement to increase course supports. Researchers need to continue to center the experiences of students with disabilities in STEM courses so that researchers and practitioners can identify disciplinarily specific strategies to support student engagement and learning.